Targeting CD30 Using Brentuximab Vedotin in the Treatment of Hodgkin Lymphoma - Alperovich, Anna (Cancer J, 2016)
The expression of CD30 receptors is one of the defining characteristics of the malignant Reed-Sternberg cells of Hodgkin lymphoma. CD30 is rarely expressed by normal cells, and is rapidly internalized, making it an ideal therapeutic target for monoclonal antibodies and for antibody-drug conjugates (ADCs). Brentuximab vedotin is the first ADC to be approved by regulatory agencies for the treatment of patients with relapsed HL, with a single agent response rate of 75%. In this review article we will discuss the current and ongoing development of brentuximab vedotin in patients with relapsed and newly diagnosed Hodgkin lymphoma.